Relationship Between Tumor Size and Neutrophil–Lymphocyte Ratio in Patients with Papillary Thyroid Carcinoma - Göksu, Mustafa; Alakuş, Hüseyin (Cerrahpaşa Medical Journal, 2022)
Objective: Inflammation plays a very important role in the stages of cancer development. In thyroid cancer, systemic inflammatory markers, such as neutr ophil –lymp hocyt e ratio, may have important potential roles in prognosis. There are conflicting studies concerning the predictive value of neutr ophil –lymp hocyt e ratio in thyroid cancer. In this study, our aim was to evaluate the correlation between clinicopathological features and neutr ophil –lymp hocyt e ratio in patients with papillary thyroid carcinoma. Methods: In this study, the records of 102 patients diagnosed with papillary thyroid carcinoma who underwent surgical treatment in the General Surgery Clinic of our hospital between March 2013 and March 2021 were retrospectively analyzed. Results: The median neutr ophil –lymp hocyt e ratio was calculated as 1.84, and the patients were divided into 2 groups as neutr ophil –lymp hocyt e ratio < 1.84 and neutr ophil –lymp hocyt e ratio ≥ 1.84. Age, gender, multifocality, bilaterality, and lymph node metastasis did not statistically significantly differ between the 2 groups. The difference in the extrathyroidal spread was close to statistical significance. There was a statistically significant difference in tumor size between the high and low neutr ophil –lymp hocyt e ratio groups. Conclusions: We found a positive correlation between neutr ophil –lymp hocyt e ratio and tumor size in patients with papillary thyroid carcinoma. In addition, in the high neutr ophil –lymp hocyt e ratio group, the presence of extrathyroidal spread was close to the significance level. Cite this article as: Göksu M, Alakuş H. Relationship between tumor size and neutr ophil –lymp hocyt e ratio in patients with papillary thyroid carcinoma. Cerrahpaşa Med J. 2023;47(1):19-22.